2008
DOI: 10.1007/s12185-008-0182-4
|View full text |Cite
|
Sign up to set email alerts
|

Study of a new indirect method based on absolute norms of variation to detect autologous blood transfusion

Abstract: The aim of this study was to investigate an indirect method based on a determination of absolute norms of variation in biological markers that could be used to identify autologous blood transfusion within the framework of the fight against doping. The selection of markers was made from experimental variations obtained during different phases including an increase in training volume at sea level, high altitude training, blood withdrawal and autologous blood reinfusion. The global statistical method was then dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…The variation in these standard blood variables after RBC transfusion that was observed in the present study was consistent with that reported in the literature [9,[23][24][25][26]. After saline infusion, several variables showed significant variation from baseline at a number of time points.…”
Section: Discussionsupporting
confidence: 92%
“…The variation in these standard blood variables after RBC transfusion that was observed in the present study was consistent with that reported in the literature [9,[23][24][25][26]. After saline infusion, several variables showed significant variation from baseline at a number of time points.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, in regard to the important implications of a positive anti-doping test for the athlete's life, we think that the norms of variation proposed by Sallet et al [1] for detecting autologous blood transfusion require extra consideration/experimentation and should not be implemented as internal regulations by the international federations yet. Moreover, we caution against the general application of the use of [Ht] and [Hb] for indirect doping makers without broad consideration for its limitations.…”
mentioning
confidence: 92%
“…In a recent manuscript published in the International Journal of Hematology, Sallet et al [1] reported absolute norms of variation established for a maximal 15 days period to distinguish autologous blood transfusion from normal modifications, using hematocrit (Ht), hemoglobin ([Hb]) and stimulation index (Off-hr) (calculated using the following equation [Hb] -60H reticulocytes in %) as markers. The thresholds the authors proposed are 6% for Ht, 4% for [Hb] and 20% for Off-hr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25] However, as some of these parameters are easily affected by dehydration or altitude training, the use of this protocol seems limited. As already mentioned, if two blood samples before and after the blood transfusion process separated by more than 15 days are obtained from the same subject, changes in haematocrit (Hct), Hb and OFFhr (Hb-60(%retic) 1/2 ) are observed, which were again proposed as the basis for this type of doping detection.…”
Section: Blood Markers Approachmentioning
confidence: 99%